Src-family kinase-Cbl axis negatively regulates NLRP3 inflammasome activation. Issue 11 (November 2018) - Chung, I-Che; Yuan, Sheng-Ning; OuYang, Chun-Nan; Lin, Hsin-Chung; Huang, Kuo-Yang; Chen, Yu-Jen; Chung, An-Ko; Chu, Ching-Liang; Ojcius, David; Chang, Yu-Sun; Chen, Lih-Chyang
Abstract Activation of the NLRP3 inflammasome is crucial for immune defense, but improper and excessive activation causes inflammatory diseases. We previously reported that Pyk2 is essential for NLRP3 inflammasome activation. Here we show that the Src-family kinases (SFKs)-Cbl axis plays a pivotal role in suppressing NLRP3 inflammasome activation in response to stimulation by nigericin or ATP, as assessed using gene knockout and gene knockdown cells, dominant active/negative mutants, and pharmacological inhibition. We reveal that the phosphorylation of Cbl is regulated by SFKs, and that phosphorylation of Cbl at Tyr371 suppresses NLRP3 inflammasome activation. Mechanistically, Cbl decreases the level of phosphorylated Pyk2 (p-Pyk2) through ubiquitination-mediated proteasomal degradation and reduces mitochondrial ROS (mtROS) production by contributing to the maintenance of mitochondrial size. The lower levels of p-Pyk2 and mtROS dampen NLRP3 inflammasome activation. In vivo, inhibition of Cbl with an analgesic drug, hydrocotarnine, increases inflammasome-mediated IL-18 secretion in the colon, and protects mice from dextran sulphate sodium-induced colitis. Together, our novel findings provide new insights into the role of the SFK-Cbl axis in suppressing NLRP3 inflammasome activation and identify a novel clinical utility of hydrocortanine for disease treatment.